System amyloidosis with predominant heart disease: own observations. - Dyadyk, O. O.; Baltonkova, O. S. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. It is difficult to diagnose amyloidosis at the early stages of disease progress due to long-term symptom-free progression. Several organs are involved in the pathologic process by AL-amyloidosis of predominant number of patients (69%); about 20% have cardiac symptoms and only in 5% of cases the isolated heart disease. Objective: identify peculiarities of heart damage by amyloidosis on the basis of morphologic study of cases with system amyloidosis and justify morphology of amyloid cardiomegaly. Methods. Material for the research was taken during corpse dissection: male - 62 years old and female - 63 years old. In the course of the research autopsy, macro-, microscopic methods, as well as histo- and immunohistochemical methods were used. Results. The amyloidosis was identified after the dissection according to specific outer appearance of organs. Specific histochemical and immunohistochemical reaction for amyloidosis detection were carried out. Taking into account pathomorphological research data and amyloid immunophenotyping, the primary (system) amyloidosis with predomination of λ-, k-light immunoglobulin chains was identified. Conclusions. The heart is the dominant target organ for systemic amyloidosis. Specification of morphological verification including histochemical and immunohistochemical methods is needed to improve diagnostic algorithms.